Minimal switching of multiple input multilevel output DC-DC converter - Amer A. Chlaihawi; Ameen Al-Modaffer; Hur Jedi (Institute of Advanced Engineering and Science, 2021)
This paper proposes a minimal switching multiple input multilevel output (MS-MIMLO) DC-DC converter. Minimizing the cost of operation is an utmost priority of any electric circuit design. Thus, reduction number of switches that control and manage the operation of feeding power into the MIMLO DC-DC convertors is presented. The proposed MS-MIMLO DC-DC converter exerts many advantages, include high voltage transfer ratio with a small size inductor, reduced power losses and low voltage stress across the semiconductor devices. Beside the highly conversion ratio and efficiency, the characteristics of the proposed converter have a simple configuration with low number of components as well. The MATLAB/Simulink software was implemented to simulate the proposed topology in order to verify the performance of the MS-MIMLO DC-DC converter. The result of simulations demonstrated the benefits of reducing the number of switches without affecting the operation and performance of the MIMLO DC-DC converter circuit.